Book review: Adam Auerbach, Demanding Development: The Politics of Public Goods Provision in India's Urban Slums. (November 2021) - Tumbe, Chinmay
Adam Auerbach, Demanding Development: The Politics of Public Goods Provision in India's Urban Slums . Cambridge: Cambridge University Press, 2020, 328pp., 34.99. ISBN: 1108491936 (hardcover). ISBN: 9781108741330 (paperback).